Two rarities together: A free peritoneal body in a hernia en pantaloon sac and case series of our experience of finding loose peritoneal bodies - Majeed, Talal; Chauhan, M. N.; Magee, Conor (Indian Journal of Case Reports, 2019)
Peritoneal loose bodies (PLBs) are rare findings that were reported extensively in the early nineteenth and twentieth century in theform of case series by Littre, Riedel and Macintosh. In the recent past, focus has shifted more towards symptomatic free peritonealbodies. Although a proper intrabdominal examination and histopathology can help to clear the diagnosis, there is still no consensusin the surgical circle as to how to deal with them. Here, we report a case series of 4 cases of finding loose peritoneal bodies duringintra-abdominal procedures, three of them were found during laparoscopic procedures (laparoscopic appendectomy, Robotic meshrectopexy and laparoscopic bowel resection) while one was an open surgery (open inguinal hernia repair). This paper is unique asfor the first time in the history it brings two surgical rarities together i.e. ‘hernia en pantaloon’ and free peritoneal body along withrecommendations based on the literature, review to diagnose and treat loose peritoneal bodies.